Clipping the (tongue) tie - Nagate Raghavendra Reddy; Yuvaraja Marudhappan; Renuka Devi; Sumit Narang (Wolters Kluwer Medknow Publications, 2014)
Ankyloglossia is an uncommon congenital oral anomaly that can cause difficulty with breast-feeding and speech articulation. For many years, the subject of ankyloglossia has been controversial with practitioners of many specialties having widely different views regarding its significance and management. This study is about a series of five cases of ankyloglossia subjected to surgical correction by frenectomy procedure. Three cases were treated with electrocautery, one case with diode laser and one case with conventional scalpel technique. 1 week and 1 month post-operative follow-ups were done and healing was compared with the available literature. Manipulation of tissues was better in laser and electrocautery techniques when compared with scalpel. Post-operative complication of swelling and pain was seen in scalpel technique whereas it was largely uneventful in other techniques. Though, there was no difference in healing at the end of first month clinically, scalpel technique has shown better results in organization of muscle fibers. This clinical study indicates that laser and electrocautery treatment used for frenectomy operations provides better patient perception in terms of postoperative pain and function than that obtained by the scalpel technique. Considering the above advantages, when used correctly, the laser and electrocautery offers a safe, effective, acceptable and impressive alternative for frenectomy operations.